Given an ODE
![x'=f(t,x)](https://tex.z-dn.net/?f=x%27%3Df%28t%2Cx%29)
with initial condition
![x(t_0)=x_0](https://tex.z-dn.net/?f=x%28t_0%29%3Dx_0)
, the general process is to write the ODE as an integral equation,
![x(t)=x_0+\displaystyle\int_{t_0}^tf(u,x(u))\,\mathrm du](https://tex.z-dn.net/?f=x%28t%29%3Dx_0%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Etf%28u%2Cx%28u%29%29%5C%2C%5Cmathrm%20du)
By setting
![x_0(t)=x_0](https://tex.z-dn.net/?f=x_0%28t%29%3Dx_0)
for all
![t](https://tex.z-dn.net/?f=t)
, we get the following recurrence for
![n\ge1](https://tex.z-dn.net/?f=n%5Cge1)
.
![x_{n+1}(t)=x_0+\displaystyle\int_{t_0}^tf(u,x_n(u))\,\mathrm du](https://tex.z-dn.net/?f=x_%7Bn%2B1%7D%28t%29%3Dx_0%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Etf%28u%2Cx_n%28u%29%29%5C%2C%5Cmathrm%20du)
From this we work towards finding a pattern for
![x_n](https://tex.z-dn.net/?f=x_n)
so that we can find a solution of the form
![x=\lim\limits_{n\to\infty}x_n](https://tex.z-dn.net/?f=x%3D%5Clim%5Climits_%7Bn%5Cto%5Cinfty%7Dx_n)
.
![\begin{cases}x'=x+2\\x(0)=2\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%27%3Dx%2B2%5C%5Cx%280%29%3D2%5Cend%7Bcases%7D)
Write this as the integral equation,
![x_{n+1}=x(0)+\displaystyle\int_{t_0}^t(x_n(u)+2)\,\mathrm du](https://tex.z-dn.net/?f=x_%7Bn%2B1%7D%3Dx%280%29%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Et%28x_n%28u%29%2B2%29%5C%2C%5Cmathrm%20du)
First step:
![x_1=x(0)+\displaystyle\int_{t_0}^t(x_0(u)+2)\,\mathrm du](https://tex.z-dn.net/?f=x_1%3Dx%280%29%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Et%28x_0%28u%29%2B2%29%5C%2C%5Cmathrm%20du)
![x_1=2\displaystyle\int_0^t\mathrm du](https://tex.z-dn.net/?f=x_1%3D2%5Cdisplaystyle%5Cint_0%5Et%5Cmathrm%20du)
![x_1=2t](https://tex.z-dn.net/?f=x_1%3D2t)
Second step:
![x_2=x(0)+\displaystyle\int_{t_0}^t(x_1(u)+2)\,\mathrm du](https://tex.z-dn.net/?f=x_2%3Dx%280%29%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Et%28x_1%28u%29%2B2%29%5C%2C%5Cmathrm%20du)
![x_2=\displaystyle\int_0^t(2u+2)\,\mathrm du](https://tex.z-dn.net/?f=x_2%3D%5Cdisplaystyle%5Cint_0%5Et%282u%2B2%29%5C%2C%5Cmathrm%20du)
![x_2=t^2+2t](https://tex.z-dn.net/?f=x_2%3Dt%5E2%2B2t)
Third step:
![x_3=x(0)+\displaystyle\int_{t_0}^t(x_2(u)+2)\,\mathrm du](https://tex.z-dn.net/?f=x_3%3Dx%280%29%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Et%28x_2%28u%29%2B2%29%5C%2C%5Cmathrm%20du)
![x_3=\displaystyle\int_0^t(t^2+2t+2)\,\mathrm du](https://tex.z-dn.net/?f=x_3%3D%5Cdisplaystyle%5Cint_0%5Et%28t%5E2%2B2t%2B2%29%5C%2C%5Cmathrm%20du)
![x_3=\dfrac13t^3+t^2+2t](https://tex.z-dn.net/?f=x_3%3D%5Cdfrac13t%5E3%2Bt%5E2%2B2t)
Fourth step:
![x_4=x(0)+\displaystyle\int_{t_0}^t(x_3(u)+2)\,\mathrm du](https://tex.z-dn.net/?f=x_4%3Dx%280%29%2B%5Cdisplaystyle%5Cint_%7Bt_0%7D%5Et%28x_3%28u%29%2B2%29%5C%2C%5Cmathrm%20du)
![x_4=\displaystyle\int_0^t\left(\frac13u^3+u^2+2u+2\right)\,\mathrm du](https://tex.z-dn.net/?f=x_4%3D%5Cdisplaystyle%5Cint_0%5Et%5Cleft%28%5Cfrac13u%5E3%2Bu%5E2%2B2u%2B2%5Cright%29%5C%2C%5Cmathrm%20du)
![x_4=\dfrac1{4\times3}t^4+\dfrac13t^3+t^2+2t](https://tex.z-dn.net/?f=x_4%3D%5Cdfrac1%7B4%5Ctimes3%7Dt%5E4%2B%5Cdfrac13t%5E3%2Bt%5E2%2B2t)
You should already start seeing a pattern. Recall that
![e^t=\displaystyle\sum_{k=0}^\infty\frac{x^k}{k!}=1+t+\frac{t^2}2+\frac{t^3}{2\times3}+\frac{t^4}{2\times3\times4}+\cdots](https://tex.z-dn.net/?f=e%5Et%3D%5Cdisplaystyle%5Csum_%7Bk%3D0%7D%5E%5Cinfty%5Cfrac%7Bx%5Ek%7D%7Bk%21%7D%3D1%2Bt%2B%5Cfrac%7Bt%5E2%7D2%2B%5Cfrac%7Bt%5E3%7D%7B2%5Ctimes3%7D%2B%5Cfrac%7Bt%5E4%7D%7B2%5Ctimes3%5Ctimes4%7D%2B%5Ccdots)
Multiplying this by 2 gives
![2e^t=2+2t+t^2+\dfrac{t^3}3+\dfrac{t^4}{4\times3}+\cdots](https://tex.z-dn.net/?f=2e%5Et%3D2%2B2t%2Bt%5E2%2B%5Cdfrac%7Bt%5E3%7D3%2B%5Cdfrac%7Bt%5E4%7D%7B4%5Ctimes3%7D%2B%5Ccdots)
which matches the solution we have for
![x_4](https://tex.z-dn.net/?f=x_4)
except for that first term. So subtracting that, we find a solution of
![x=2e^t-2](https://tex.z-dn.net/?f=x%3D2e%5Et-2)
with a domain of
![t\in\mathbb R](https://tex.z-dn.net/?f=t%5Cin%5Cmathbb%20R)
.
Hopefully this gives some insight on how to approach the other two problems.